Metal-organic framework (MOF)-bioactive glass (BG) systems for biomedical applications - A review - Andrada-Ioana Damian-Buda; Nariman Alipanah; Faina Bider; Orhan Sisman; Zuzana Neščáková; Aldo R. Boccaccini (Materials Today Bio)
In recent years, metal-organic frameworks (MOFs) have emerged as promising materials for biomedical applications, owing to their superior chemical versatility, unique textural properties and enhanced mechanical properties. However, their fast and uncontrolled degradation, together with the reduced bioactivity have restricted their clinical potential. To overcome these limitations, MOFs can be synergistically combined with other materials, such as bioactive glasses (BGs), known for their bioactivity and therapeutic ion releasing capabilities. Besides comparing MOFs and BGs, this review aims to present the latest achievements of different MOFs/BGs materials, with a particular focus on their complementary and synergistic properties. Key findings show that combining MOFs and BGs enables the development of composite materials with superior physicochemical and biological properties. Moreover, by choosing appropriate processing techniques, BGs and MOFs can be fabricated as scaffolds or coatings with fast mineralization ability and high corrosion resistance. In addition, incorporation of MOFs/BGs in hydrogels improves mechanical stability, bioactivity and antibacterial properties, while maintaining biocompatibility. The mechanisms behind the antibacterial properties, likely coming from the release of metal ions and organic ligands, are also discussed. Overall, this review highlights the current research directions and emerging trends in the synergistic use of MOFs and BGs for biomedical applications, which represents a novel strategy for developing a new family of advanced therapeutic materials.